Natural products, including a new caboxamycin, from Streptomyces and other Actinobacteria isolated in Spain from storm clouds transported by Northern winds of Arctic origin - Sarmiento-Vizcaíno, Aida; Martín, Jesús; Ortiz-López, Francisco Javier; Reyes, Fernando; García, Luis A.; Blanco, Gloria (Frontiers in Chemistry, 2022)
Actinobacteria, mostly Streptomyces species, are the main source of natural products essential in medicine. While the majority of producer microorganisms of secondary metabolite are reported from terrestrial or marine environments, there are limited reports of their isolation from atmospheric precipitations. Clouds are considered as atmospheric oases for microorganisms and there is a recent paradigm shift whereby atmospheric-derived Actinobacteria emerge as an alternative source for drug discovery. In this context, we studied a total of 18 bioactive Actinobacteria strains, isolated by sampling 9 precipitation events with prevailing Northern winds in the Cantabrian Sea coast, Northern Spain. Backward trajectories meteorological analyses indicate that air masses were originated mostly in the Arctic Ocean, and their trajectory to downwind areas involved the Atlantic Ocean and also terrestrial sources from continental Europe, and in some events from Canada, Greenland, Mauritania and Canary Islands. Taxonomic identification of the isolates, by 16S rRNA gene sequencing and phylogenetic analyses, revealed that they are members of three Actinobacteria genera. Fifteen of the isolates are Streptomyces species, thus increasing the number of bioactive species of this genus in the atmosphere to a 6.8 % of the total currently validated species. In addition, two of the strains belong to the genus Micromonospora and one to genus Nocardiopsis. These findings reinforce a previous atmospheric dispersal model, extended herein to the genus Micromonospora. Production of bioactive secondary metabolites was screened in ethyl acetate extracts of the strains by LC-UV-MS and a total of 94 secondary metabolites were detected after LC/MS dereplication. Comparative analyses with natural products databases allowed the identification of 69 structurally diverse natural products with contrasted biological activities, mostly as antibiotics and antitumor agents, but also anti-inflammatory, antiviral, antiparasitic, immunosuppressant and neuroprotective among others. The molecular formulae of the 25 remaining compounds were determined by HRMS. None of these molecules had been previously reported in natural product databases indicating potentially novel metabolites. As a proof of concept, a new metabolite caboxamycin B (1) was isolated from the culture broth of Streptomyces sp. A-177 and its structure was determined by various spectrometric methods. To the best of our knowledge, ...